2014
DOI: 10.1177/0333102414554661
|View full text |Cite
|
Sign up to set email alerts
|

Study of neurovascular coupling during cold pressor test in patients with migraine

Abstract: The absence of the effect of CPT on VEFR in migraine is likely to be a consequence of impaired subcortical modulation of neurovascular coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Sixteen studies compared MBFV in the posterior circulation of migraineurs and controls. 12 , 1921,23–26,29,33,35,41,4547,49 Abernathy et al., Chernyshev et al. and Karadas et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen studies compared MBFV in the posterior circulation of migraineurs and controls. 12 , 1921,23–26,29,33,35,41,4547,49 Abernathy et al., Chernyshev et al. and Karadas et al.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-five studies were identified from the literature search that compared resting mean blood flow velocity (MBFV) in migraineurs to controls; 12,16–49 30 studies assessed MBFV in the anterior circulation. 12,1924,2632,34–49 All but four studies found no significant difference in MBFV in the anterior circulation between migraineurs and controls; Abernathy et al., Fiermonte et al., Karadas et al. and Kastrup et al.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, appropriate side selection of region of interest is important in studies on NVC in migraine as pathophysiological mechanism might be asymmetrical and therefore more or less lateralized [ 64 ]. Our study has shown that cold pressor test has no effect on VEFR in patients with migraine, whereas in healthy subjects it causes an increase, suggesting dysfunctional NVC in migraine under tonic pain condition [ 65 ]. We have speculated this to be due to dysfunction of subcortical modulatory projections involved in the regulation of microvascular tone.…”
Section: Neurovascular Coupling Between Migraine Attacksmentioning
confidence: 99%
“…9,10 In contrast, studies of vascular reactivity, including those of the trigeminovascular response, 3,11,12 have shown promise in the study of migraine, with evidence to suggest altered vascular function both extra-and intracranially. [13][14][15] In recent decades, several optical techniques have been developed for noninvasive and noncontact blood perfusion imaging, including laser Doppler flowmetry (LDF), laser speckle contrast techniques, optical imaging, and photoplethysmography; however, recent applications to facial structures have focused on pulsatility 16,17 and surrogate markers for systemic cardiovascular function (heart rate, blood pressure (BP)). [18][19][20] In an effort to better examine intrinsic vascular function of the craniofacial region, we developed a technique adapted from our work in animal model systems, 21,22 utilizing surface imaging to register spontaneous oscillatory hemodynamic changes in the skin (facial cutaneous oscillations (FCOs)) to examine differences in facial blood volume in response to trigeminovascular reflex stimulation, as well as standardized measures of cardiovascular autonomic function (heart rate variability and baroreflex responses).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In contrast, studies of vascular reactivity, including those of the trigeminovascular response, 3,11,12 have shown promise in the study of migraine, with evidence to suggest altered vascular function both extra- and intracranially. 13 15…”
Section: Introductionmentioning
confidence: 99%